Grounding IPBES experts’ views on the multiple values of nature in epistemology, knowledge and collaborative science - Hakkarainen, Viola (2020)
This study identifies and analyses the underlying assumptions of experts involved in the first author meeting (FAM) of the Intergovernmental Science-Policy Platform on Biodiversity and Ecosystem Services (IPBES)’s Values Assessment, and how they shape understandings of the multiple values of nature. We draw from survey data collected from 94 experts attending the FAM. Respondents self-report the tendencies and aims they bring to the assessment (i.e. motivation), the type and amount of evidence they require for knowledge to be valid (i.e. confirmation) and their epistemic worldviews (i.e. objectivity). Four clusters emerged that correspond to Pragmatist, Post-Positivist, Constructivist and Transformative epistemic worldviews. This result clarifies how different knowledge claims are represented in science-policy processes. Despite the proportionately higher number of social scientists in the Values Assessment, compared with previous IPBES assessments, we still found that fewer experts have Constructivist or Transformative worldviews than Pragmatist or Post-Positivist outlooks, an imbalance that may influence the types of values and valuation perspectives emphasised in the assessment. We also detected a tension regarding what constitutes valid knowledge between Post-Positivists, who emphasised high levels of agreement, and Pragmatists and Constructivists, who did not necessarily consider agreement crucial. Conversely, Post-Positivists did not align with relational values and were more diverse in their views regarding definitions of multiple values of nature compared to other clusters. Pragmatists emphasized relational values, while Constructivists tended to consider all value types (including relational values) as important. We discuss the implications of our findings for future design and delivery of IPBES processes and interdisciplinary research.